Relationship Between Fatty Acid Concentrations in Wine Yeasts and Sugar Fermentation at Different Temperatures - Venter, J.J.; van Vuuren, H.J.J.; Tromp, A.; Randal, J.H. (South African Journal of Enology and Viticulture, 2017)
The effects of temperature and fermentation stage on the cellular concentrations of unsaturated and saturated fatty acids on the fermentation abilities of four differentSaccharomyces cerevisiae wine yeasts were studied at three temperatures. The total unsaturated and saturated fatty acid concentrations were determined at six fermentation stages. Unsaturated fatty acid concentration decreased and the concentration of saturated fatty acids increased as fermentation proceeded. Saturated fatty acid concentration of the yeast cells correlated positively with high specific fermentation rates during the later stages of fermentation in contrast to the belief that fluid membranes with high unsaturated fatty acid concentrations enhance ethanol tolerance and, therefore, fermentation performance.